2021
DOI: 10.1002/adma.202007982
|View full text |Cite
|
Sign up to set email alerts
|

From Understanding Mechanical Behavior to Curvature Prediction of Humidity‐Triggered Bilayer Actuators

Abstract: Nature will always be an endless source of bioinspiration for man‐made smart materials and multifunctional devices. Impressively, even cutoff leaves from resurrection plants can autonomously and reproducibly change their shape upon humidity changes, which goes along with total recovery of their mechanical properties after being completely dried. In this work, simple bilayers are presented as autonomously moving, humidity‐triggered bending actuators. The bilayers—showing reproducible bending behavior with rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…Recent demonstrations and theoretical predictions showed that such WR actuation could be extremely powerful and efficient, [7][8][9] inspiring the growing studies and development of WR structures for actuators and artificial muscles. [10][11][12][13][14][15][16][17] Notable WR examples include a titanium oxide film [18] and a twisted carbon nanotube yarn, [19] which exhibit WR energy densities of ≈1250 and 1800 kJ m −3 (2.17 kJ kg −1 ), respectively. Microrobots equipped with WR actuators of 𝜋-stacked carbon nitride films [8] and polyethylene oxide nanofibers [20] have been demonstrated to exhibit autonomous locomotion powered by fluctuations in ambient RH.…”
Section: Doi: 101002/advs202104697mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent demonstrations and theoretical predictions showed that such WR actuation could be extremely powerful and efficient, [7][8][9] inspiring the growing studies and development of WR structures for actuators and artificial muscles. [10][11][12][13][14][15][16][17] Notable WR examples include a titanium oxide film [18] and a twisted carbon nanotube yarn, [19] which exhibit WR energy densities of ≈1250 and 1800 kJ m −3 (2.17 kJ kg −1 ), respectively. Microrobots equipped with WR actuators of 𝜋-stacked carbon nitride films [8] and polyethylene oxide nanofibers [20] have been demonstrated to exhibit autonomous locomotion powered by fluctuations in ambient RH.…”
Section: Doi: 101002/advs202104697mentioning
confidence: 99%
“…Recent demonstrations and theoretical predictions showed that such WR actuation could be extremely powerful and efficient, [ 7 , 8 , 9 ] inspiring the growing studies and development of WR structures for actuators and artificial muscles. [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Another kind of actuating and sensing system is based on actuating materials with sensing/perception functions, [ 6 , 7 , 8 ] which can respond to external stimuli such as light, [ 9 , 10 ] electricity, [ 11 , 12 ] temperature, [ 13 , 14 ] and humidity. [ 15 , 16 ] However, these actuating and sensing systems lack the response to mechanical stimuli, which limits their application in bionic systems and human–computer interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional bilayer actuator can only be driven by a single stimulus, such as light, [6][7][8] electricity, [9][10][11] humidity. [12][13][14] For example, Weng and coworkers proposed an electrothermal actuator based on graphite/polyaniline paper-like composites. The electrothermal actuator exhibited a large bending motion (bending curvature >1 cm À1 ) with an ultralow driving voltage of 2.5 V. 15 Hu and coworkers reported untethered soft light-driven actuators based on covalently-bridged black phosphorus-carbon nanotubes (CNT) heterostructure with self-oscillation and phototactic locomotion under light irradiation.…”
Section: Introductionmentioning
confidence: 99%